Courage & Compromise - Bly, Stephen A 1944- (Wheaton, Ill. : Crossway Books, 2003)
The lives of the Bowers family are tried when heavy rain damages their house, Mr. Bowers get arrested for rioting, and Jolie's relationship with Tanner is troubled following the arrival of a handsome widower.